Democratic Republic of the Congo : Staff Report for the 2005 Article IV Consultation Fifth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility Requests for Waiver of Performance Criteria Additional Interim Assistance Under the Enhanced Initiative for Heavily Indebted Poor Countries and Request for an Extension of Arrangement. (IMF Staff Country Reports; Country Report, 2005)
This 2005 Article IV Consultation highlights that the economic activity in the Democratic Republic of the Congo (DRC) started to recover in 2002, after declining for 13 years. Inflation declined from 511 percent at end-2000 to 4 percent at end-2003. Fiscal developments were mixed in 2004, with government revenue higher and expenditure lower than programmed. The main risks for the rest of 2005 relate to security and social tensions, which could worsen in the case of further delays in the transition process.